Modern Technologies and Transformation of Social Work Profession and Education: Insights of Teachers of the Lithuanian and Japanese Higher Education Institutions - Žalimienė, Laimutė; Charenkova, Juratė; Šumskienė, Eglė; Petružytė, Donata; Seniutis, Miroslavas; Gevorgianienė, Violeta; Yamaguchi, Mai (Socialinė teorija, empirija, politika ir praktika, 2022)
This article explores the attitudes of Japanese and Lithuanian social work program teachers towards the challenges posed by modern technologies that may transform social work profession and studies. Study data revealed that scientists from both countries admit that “taming” technologies and optimally “cooperating” with them is the main challenge of social work practice and studies. On the one hand, belief that technological development will provide more opportunities to fulfil the mission of social work was prevalent among the study participants, on the other hand, they had expressed concern that eventually the use of technology will change the essence of social work as a profession of human relations or will create modified forms of social exclusion. Additionally, a niche for the new role of the social worker was identified: to help the world “occupied” by technology remain “social”. Attitudes of research participants from both Lithuania and Japan can be linked to traditional concept of sociality and vision of social work as profession that belongs exclusively to area of human relations. B. Latour’s asocial sociality concept can be applied for broader look into this situation. This concept states that efforts to trace the contribution of actors of an inhuman nature to what belongs in the human world may be more successful when one ceases to view the world exclusively through human eyes and tries to reveal the inner perspectives of phenomena of a mixed nature.